1996
DOI: 10.1128/mcb.16.10.5839
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of Raf-1 by Geldanamycin Leads to Disruption of the Raf-1–MEK–Mitogen-Activated Protein Kinase Signalling Pathway

Abstract: The serine/threonine kinase Raf-1 functions downstream of Ras in a signal transduction cascade which transmits mitogenic stimuli from the plasma membrane to the nucleus. Raf-1 integrates signals coming from extracellular factors and, in turn, activates its substrate, MEK kinase. MEK activates mitogen-activated protein kinase (MAPK), which phosphorylates other kinases as well as transcription factors. Raf-1 exists in a complex with HSP90 and other proteins. The benzoquinone ansamycin geldanamycin (GA) binds to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 255 publications
(179 citation statements)
references
References 52 publications
8
170
0
1
Order By: Relevance
“…Previous studies have shown that HSP90 was required for the stabilization and appropriate intracellular localization of Raf (Schulte et al, 1995(Schulte et al, , 1996. The observations of (Soga et al, 1998) suggested that radicicol treatment of K-Ras transformed cells resulted in the destabilization of Raf-1.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Previous studies have shown that HSP90 was required for the stabilization and appropriate intracellular localization of Raf (Schulte et al, 1995(Schulte et al, , 1996. The observations of (Soga et al, 1998) suggested that radicicol treatment of K-Ras transformed cells resulted in the destabilization of Raf-1.…”
Section: Resultsmentioning
confidence: 94%
“…Molecular chaperones such as HSP90 play a major role in cellular homeostasis by aiding in the proper folding and localization of a number of key proteins (reviewed in Johnson and Craig, 1997). The association of Raf-1 with the molecular chaperones HSP90 and cdc37/p50 appears to play a critical role in maintaining the stability and membrane localization of Raf (Schulte et al, 1995(Schulte et al, , 1996. In particular, HSP90 binding agents such as the benzoquinone ansamycin, geldanamycin, promotes ± 4), pre-incubated ®rst with geldanamycin followed by KT8529 (lanes 6 ± 9) or pre-incubated ®rst with UCS1006 followed by KT8529 (lanes 11 ± 14) as indicated at the bottom of the autoradiograms and as described in the Materials and methods section.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations